Effect of Maggot Flour (Hermetia illucens larvae) on Histopathology of Koi carp (Cyprinus carpio) Muscles and Gills Infected with Edwarsiella tarda - Hengki Pradana; Arief Prajitno; Maftuch Maftuch (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research